SYSTEMATIC ANALYSIS OF INVARIANCE OF SEPARATE CONTROL CIRCUITS OF HIGH-SPEED ROLLING WITH A LOOP ON CONTINUOUS SMALL SECTION MILL (Modern Problems of Metallurgy, 2025)
The condition of the rolled products in the interstand gaps of continuous small-section mills is determined by the difference in rolling speeds at the exit from the previous stand and at the entrance to the next stand. A change in the rolling speed in any of the stands in the gap, arising under the action of process disturbances, leads to a deviation from the initial rolling mode in this gap. Elimination of such a deviation is achieved by targeted correction of the roll speed of one of the stands. However, this disrupts the speed mode in the adjacent interstand gap along the rolling direction, which activates the tension control circuit in it, and then in the subsequent gaps, which can destabilize the operation of the entire mill. To solve this problem, when changing the roll speed of one of the stands of the continuous group, it is necessary to simultaneously change the roll speed of all subsequent (along the rolling direction) or all previous (counter-rolling direction) stands. Computer modeling of the functioning of the high-speed rolling mode control system in a group of stands confirmed the effectiveness of the proposed method, based on a systematic analysis of the invariance of the operation of separate circuits of the rolling loop position stabilization.
Keywords: continuous small-section mill; speed mode; rolling with a loop; separate control circuits.